Análise experimental da capacidade de regeneração da eficiência da redução de arrasto por polímeros - Cussuol, Jordan Deambrosio (2023)
The phenomenon known as drag reduction (DR) provided by the addition of high molecular weight polymers in turbulent flows has been widely investigated since its discovery for over 70 years. The DR promotes a significant decrease of the friction factor and increase the efficiency of several industrial processes. However, the drag reduction efficiency is not constant. The interaction between the turbulent eddies of the flow with the polymer molecules causes mechanical degradation and/or de-aggregation of the polymer chains. Mechanical degradation is the mechanical scission of the intramolecular links of polymer chains, while de-aggregation is the breaking of the intermolecular links of the aggregates (polymer structures formed by the link of two or more molecular chains). There are many studies on the literature that extensively investigate the mechanical polymer degradation and its important influence variables. However, there are still important aspects that need more studies for a better understanding of this phenomenon, such as the polymer de-aggregation mechanism and the possibility the recovery of aggregates in a polymeric solution (polymer re-aggregation). Possibly, the re-aggregation of polymer chains promotes the drag reduction regeneration. Thus, the objective of this work is to investigate the polymer de-aggregation and the possibility of drag reduction regeneration. For this, the drag reduction tests will be carry out in a rotating cylindrical Taylor-Couette rheometer device. The polymer de-aggregation and drag reduction regeneration are evaluated for three different polymers: Poly(ethylene oxide) (PEO), Polyacrylamide (PAM) and Xanthan Gum (XG). The first two are known as flexible molecules while the last one is considered rigid. The results show that the polymer de-aggregation plays an important role in the loss of polymer drag reduction efficiency. When the additives are flexible polymers (PEO and PAM), the mechanical degradation and de-aggregation have the same relevance to the loss of drag reduction efficiency. In the case of XG (rigid polymer), the loss of drag reduction efficiency is exclusively related to de-aggregation. Furthermore, the results also indicate that polymer de-aggregation is not permanent. After de-aggregation, the polymer molecules re-aggregate over time, regenerating the drag reduction efficiency.